Are technology parks the same? A typology proposal for an emerging economy - Rodrigo Bolliger; Bruno Brand\~ao Fischer; Marcelo G. Amaral; Adriana Ferreira de Faria; Milena Pavan Serafim (Innovation & Management Review, 2025)
Recent literature has increasingly analyzed Science and Technology Parks (STPs) as heterogeneous ecosystems. However, studies on STPs in emerging countries remain limited. This study aims to develop a typology of STP profiles based on their distinctive characteristics in a developing country and to compare these profiles with the context of developed countries.An exploratory methodology was adopted to identify STP profiles in the Brazilian context. The analysis focused on four dimensions associated with their configurations: structural characteristics, knowledge generation, resource availability and local context. Cluster analysis was conducted using SPSS software.The study identifies three distinct clusters of STPs: University-Based, Legitimator and Firms-Hotel. These clusters differ significantly in terms of resource provision, associations with research centers and universities and age.The study is constrained by the sample size. Furthermore, it does not explore differences in the operational dynamics of the clusters over time.The findings demonstrate that Brazilian STPs are composed of diverse elements, highlighting the need for policies and strategies that move beyond assumptions of structural isomorphism. Such policies and strategies should focus on resource complementarity with local capacities. The research also underscores the potential of using clustering methodologies as a foundation for evaluating the impact of STPs on the performance of tenant firms.This study contributes to the literature by emphasizing the heterogeneous nature of STPs in emerging economies and differences to developed countries context.
Keywords: 650; Science and technology parks; Brazil; Cluster analysis; Heterogeneity